DEVELOPMENT OF FUN THINKERS BOOK LEARNING MEDIA ON THE MATERIAL INVERTEBRATA CLASS X SMA NEGERI 12 BONE - Ahmad Ali; Hamansah; Ainul Dzakina (Journal of Islam and Science, 2022)
Fun thinkers book learning media is a collection of several game sheets packaged in a set of books full of educational activities, and quizzes to hone students' thinking skills and make learning activities more enjoyable. Fun thinkers book learning media has several advantages such as encouraging students to participate in learning, focusing attention, increasing student activities and learning outcomes. Thisresearch is a type of research and development (Research and Development) that uses the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) development model. This study aims to develop fun thinkers book learning media on Invertebrata material as a valid, practical, and effective learning media. The product developed is in the form of a fun thinkers book learning media which is tested through validity tests, practicality tests, and effectiveness tests. The subjects of this study were students of class X Science 2 SMA Negeri 12 Bone which totaled 25 people. Research instruments in the form of validation sheets to obtain product validity data, questionnaires of student and educator responses to obtain product practicality data, and learning outcomes test items to obtain product effectiveness. The results of the research showed that the fun thinkers book learning media on the Invertebrata material developed had a validity level of 3.63 with a very valid category. Assessment of student responses and educator responses with practicality levels is in the practical category with an average total score of 4.8. The test of student learning outcomes using fun thinkers book learning media on Invertebrata material is categorized as very effective because it reaches 92% of the completeness value. So that the fun thinkers book learning media that is worth using because it meets the criteria of being valid, practical, and effective